A Note on Estimating Tax Elasticities - Planning Commission (Planning Commission, 2002)
Pronab Sen’s note on estimating tax elasticities examines the responsiveness of tax revenues to changes in the tax base, a crucial factor in fiscal planning and economic policy. The paper critiques prevalent estimation methods, particularly the widely used proportional adjustment method, highlighting its systematic biases arising from discretionary tax changes and flawed data cleaning. Sen reviews alternative approaches, including constant rate structures, Divisia index methods, and econometric models, assessing their strengths and limitations. To address these issues, the paper proposes a refined methodology that calibrates tax estimates using actual revenue data and ratios of estimated to actual receipts, improving accuracy while preserving essential elements of existing methods. The study underscores the importance of methodological rigor and accurate forecasting in enhancing the reliability of tax elasticity estimates for effective public finance management.
Planning Commission Government of India November 2002
Planning Commission Government of India November 2002
Keywords: Tax Elasticity; Public Finance; Proportional Adjustment Method; Constant Rate Structure; Divisia Index; Econometric Models; Revenue Responsiveness; Budget Estimates; Discretionary Tax Changes; Data Calibration; Forecasting Accuracy; Fiscal Planning